The geology of the Shamrocke Mine and surrounding area, Rhodesia - Kyle, Derek Lyndon (Rhodes University, Faculty of Science, Department of Geology, 1972)
The geology of the Shamrocke area is described relative to its regional setting and position within the stratigraphic succession of the Lomagundi System. The stratigraphy in the immediate vicinity of the Shamrocke Mine is detailed and discussed relative to the work of others south of the project area and in other regions. The petrography of the rocks of the Shamrocke Mine area is described and the results of a great deal of mineralogical work recorded. Maps of the project area are presented at various scales from field and photogeological evidence. The thesis area is situated on the South Zambezi Escarpment of Rhodesia, and the geology described included the basaI succession of the Lomagundi System and the pre-Lomagundi Escarpment Series. The Shamrocke Mine is located on a copper orebody associated with a granulite or granofels zone within the Dolomite Series of the Lomagundi System. This ore zone granulite appears to be a metasomatised calcareous grit some 1000 feet above the upper contact of the Deweras Series (basal Lomagundi) and, within the graphitic schist and phyllite, below a dolomitic horizon in the Dolomite Series. The Lomagundi succession in the Mine area unconformably overlies the pre-Lomagundi gneiss and meta-arkose of the older, metamorphosed and deformed Escarpment Series. The basal meta-arkose, meta-quartzite and coarse schist of the Deweras Series ascends southwards through the Dolomite Series (graphitic phyllite and schist, granulite, calcareous grit, dolomite, limestone), and the Argillaceous Series (schist, phyllite, quartzite), the beds dipping steeply to the south at an angle of between 50Âº and 70Âº. Post-Lomagundi plagioclase amphibolite (altered, intrusive meta-diabase) forms Iarge semi-concordant and transgressive sills throughout the area, particularly along the contact between the Deweras and Dolomite Series. The Shamrocke Mine is on the northern limb of a large synclinal structure, the Rusere Syncline, which forms a large embayment of Lomagundi rocks into the pre-Lomagundi gneisses and granodiorites northeast from the Mine. The fold is overturned to the east and southeast. The copper mineralisation within the area and in the areas to the south is considered to be invariably associated with the basal rocks of the Lomagundi System. It occurs within both the Deweras and Dolomite Series rocks and more often than not Iies close to the contact between these two Series. The sulphide mineralisation of the Shamrocke orebody is considered, from the results of the present study, to be metasomatically emplaced during carbonate metasomatism, either from an extraneous source or from within the ore zone rock itself. The present writer favours the origin of the copper sulphide to be original syngenetic sulphide of the basal rocks of the Lomagundi depository, which has been mobilised and metasomatically relocated, possibly by the effects of regional metamorphism related to intense deformation. It is perhaps not fortuitous that the majority of the copper occurrences in the area occur where the basaI beds of the succession have been cross-folded. The copper ore comprises a simple suite of minerals, the main constituents being chalcopyrite, cubanite and pyrrhotite. The deposit is compared relative to the other copper deposits of the Lomagundi System.
Keywords: Shamrocke Mine -- Zimbabwe; Copper mines and mining -- Zimbabwe; Copper ores -- Zimbabwe; Formations (Geology) -- Zimbabwe; Petrology -- Zimbabwe; Geology -- Zimbabwe; Mineralogy -- Zimbabwe